Penjatuhan Hukuman Cambuk Terhadap Pelaku Pelecehan Seksual Terhadap Anak - Muslim Zainuddin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2023)
Decision Number 6/JN/2023/MS.Lsk sentenced perpetrators of sexual abuse of children to be whipped 35 times. This sentence is different from the Supreme Court Circular and the Attorney General Circular which require prison sentences for perpetrators if the victim is a child in cases of sexual abuse and rape. The research aims to analyze why the panel of judges sentenced them to caning and how to protect children. The research method used is normative juridical research method. The primary legal material is in the form of decision Number 6/JN/2023/MS.Lsk, Jinayat Law Qanun and Jinayat Procedural Law Qanun. Data analysis was carried out qualitatively by providing an interpretation of primary legal materials and secondary legal materials. The results of the study show that the imposition of caning punishment on perpetrators of sexual harassment whose victims are children has not been in favor of child protection. The imposition of caning was in accordance with the QHJ and QHAJ, because the judge was given the authority to impose a sentence according to the prosecutor's demands or differently. However, this does not pay attention to SEMA Number 10 of 2020 which wants prison sentences for perpetrators of sexual abuse of children.